2022
DOI: 10.3389/fcvm.2021.804111
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Matrix Metalloproteinase-1 Associates With Mitral Valve Leaflet Disruption Following Percutaneous Mitral Valvuloplasty

Abstract: Mitral regurgitation (MR) is a major complication of the percutaneous mitral valvuloplasty (PMV). Despite high technical expertise and cumulative experience with the procedure, the incidence rate of severe MR has not decreased. Although some of MR can be anticipated by echocardiographic analysis; leaflet tearing, which leads to the most dreaded type of MR, remains unpredictable. Irregular valvular collagen remodeling is likely to compromise tissue architecture and increase the tearing risk during PMV balloon i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…This may have an implication for myocardial remodelling and fibrosis during this condition [ 114 ]. Regarding rheumatic heart disease, despite several works found an increased expression of MMP-1 and MMP-9 in the mitral valve [ 115 ] and/or serum [ 116 , 117 , 118 ] of patients compared to controls, correlated with the underlying inflammation, there is currently no single study that explored a possible influence of sex on MMP expression. Sex-related differences in MMPs in patients affected by CVDs are summarized in Table 3 .…”
Section: Sex Differences In Mmps and Pathologiesmentioning
confidence: 99%
“…This may have an implication for myocardial remodelling and fibrosis during this condition [ 114 ]. Regarding rheumatic heart disease, despite several works found an increased expression of MMP-1 and MMP-9 in the mitral valve [ 115 ] and/or serum [ 116 , 117 , 118 ] of patients compared to controls, correlated with the underlying inflammation, there is currently no single study that explored a possible influence of sex on MMP expression. Sex-related differences in MMPs in patients affected by CVDs are summarized in Table 3 .…”
Section: Sex Differences In Mmps and Pathologiesmentioning
confidence: 99%
“…Left atrial (LA) thrombosis is a common complication with RHD and mitral stenosis (MS) (241). As early as 1991, the luminol-enhanced chemiluminescence technique was used to study the production of oxygen free radicals (OFR) by monocytes and neutrophils in the peripheral blood of patients with RF and RHD (242). It has been observed that in RHD patients, phagocytes are capable of penetrating the myocardium and possibly contributing to the development of cardiac injury by generating OFR (242).…”
Section: Rheumatic Heart Disease (Rhd)mentioning
confidence: 99%
“…As early as 1991, the luminol-enhanced chemiluminescence technique was used to study the production of oxygen free radicals (OFR) by monocytes and neutrophils in the peripheral blood of patients with RF and RHD (242). It has been observed that in RHD patients, phagocytes are capable of penetrating the myocardium and possibly contributing to the development of cardiac injury by generating OFR (242). In a clinical study of mitral valve resection in patients with rheumatic MS, histological studies have revealed a positive correlation between the degree of infiltration of inflammatory cells in valve tissue and the levels of MMP-1 and IFN-γ.…”
Section: Rheumatic Heart Disease (Rhd)mentioning
confidence: 99%